Selbst und Schizophrenie - Fuchs, Thomas (Deutsche Zeitschrift für Philosophie, 2012)
Current phenomenological approaches consider schizophrenia as a fundamental disturbance of the embodied self, or a disembodiment. This includes (1) a weakening of the basic sense of self, (2) a disruption of implicit bodily functioning, and (3) a disconnection from the intercorporality with others. As a result of this disembodiment, the pre-reflective, practical immersion of the self in the shared world is lost. Instead, the relationship of self and world is in constant need of reconstruction by deliberate efforts, leading to the growing perplexity and hyperreflexive ruminations that are found in schizophrenic patients. The paper distinguishes different levels of self-experience and relates it to the psychopathology of schizophrenia.